The associations between adult body composition and abdominal adiposity outcomes, and relative weight gain and linear growth from birth to age 22 in the Birth to Twenty Plus cohort, South Africa - Prioreschi, Alessandra; Munthali, Richard J.; Kagura, Juliana; Said-Mohamed, Rihlat; De Lucia Rolfe, Emanuella; Micklesfield, Lisa K.; Norris, Shane A. (PLOS ONE, 2018)
Background The growing prevalence of overweight and obesity in low- or middle-income countries precipitates the need to examine early life predictors of adiposity. Objectives To examine growth trajectories from birth, and associations with adult body composition in the Birth to Twenty Plus Cohort, Soweto, South Africa. Methods Complete data at year 22 was available for 1088 participants (536 males and 537 females). Conditional weight and height indices were generated indicative of relative rate of growth between years 0–2, 2–5, 5–8, 8–18, and 18–22. Whole body composition was measured at year 22 (range 21–25 years) using dual energy x-ray absorptiometry (DXA). Total fat free soft tissue mass (FFSTM), fat mass, and abdominal visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) were recorded. Results Birth weight was positively associated with FFSTM and fat mass at year 22 (β = 0.11, p<0.01 and β = 0.10, p<0.01 respectively). Relative weight gain from birth to year 22 was positively associated with FFSTM, fat mass, VAT, and SAT at year 22. Relative linear growth from birth to year 22 was positively associated with FFSTM at year 22. Relative linear growth from birth to year 2 was positively associated with VAT at year 22. Being born small for gestational age and being stunted at age 2 years were inversely associated with FFSTM at year 22. Conclusions The importance of optimal birth weight and growth tempos during early life for later life body composition, and the detrimental effects of pre- and postnatal growth restriction are clear; yet contemporary weight-gain most strongly predicted adult body composition. Thus interventions should target body composition trajectories during childhood and prevent excessive weight gain in early adulthood.